Implementing Islamic concept on CSR program of Pertamina in Yogyakarta - Adhianty Nurjanah; Nano Prawoto; Ilham Ramdana (Jurnal Studi Komunikasi, 2023)
This research focuses on discussing how the role of Public Relations PT. Pertamina builds reputation through SMEPP program CSR activities for Joglo Ayu Tenan MSMEs and analysed with an Islamic perspective. The research approach used is qualitative descriptive with case study research methods. Data collection techniques are carried out through in-depth interviews, literature reviews, and document studies. The results showed that PT Pertamina's PR in the implementation of CSR has carried out the value of Islamic perspective and is in accordance with the three elements of CSR implementation, namely accountability, sustainability, and transparency. As for after being studied based on an Islamic perspective, PT Pertamina's CSR implementation has carried out Islamic values, including Al-Adl shown that the beneficiaries of the CSR program are carried out fairly to the beneficiary MSMEs and do not discriminate, Al-Ihsan is realised that the SMEPP CSR Program for Joglo Ayu Tenan MSMEs is the company's concrete contribution in this case to help MSMEs by doing good, from the capital process without usury, coaching, to organising exhibitions to increase MSME sales. The value of benefits by providing coaching and training that focuses on empowerment for national economic recovery, as well as the Amanah element which is realised that the Joglo Ayu Tenan CSR Program is an implementation of the mandate of Law Number 40 of 2007 concerning Limited Liability Companies, then derived in Government Regulation No. 47 of 2012 concerning Corporate Social Responsibility (CSR) and Islamic practices.